Heat shock protein 90 (Hsp90) inhibition targets canonical TGF-β signalling to prevent fibrosis. Issue 6 (9th May 2013) - Tomcik, Michal; Zerr, Pawel; Pitkowski, Jana; Palumbo-Zerr, Katrin; Avouac, Jérôme; Distler, Oliver; Becvar, Radim; Senolt, Ladislav; Schett, Georg; Distler, Jörg H
Abstract : Objectives: Targeted therapies for systemic sclerosis (SSc) and other fibrotic diseases are not yet available. We evaluated the efficacy of heat shock protein 90 (Hsp90) inhibition as a novel approach to inhibition of aberrant transforming growth factor (TGF)-β signalling and for the treatment of fibrosis in preclinical models of SSc. Methods: Expression of Hsp90 was quantified by quantitative PCR, western blot and immunohistochemistry. The effects of Hsp90 inhibition were analysed in cultured fibroblasts, in bleomycin-induced dermal fibrosis, in tight-skin (Tsk-1) mice and in mice overexpressing a constitutively active TGF-β receptor I (TβRI). Results: Expression of Hsp90β was increased in SSc skin and in murine models of SSc in a TGF-β-dependent manner. Inhibition of Hsp90 by 17-dimethylaminoethylamino-17-demethoxy-geldanamycin (17-DMAG) inhibited canonical TGF-β signalling and completely prevented the stimulatory effects of TGF-β on collagen synthesis and myofibroblast differentiation. Treatment with 17-DMAG decreased the activation of canonical TGF-β signalling in murine models of SSc and exerted potent antifibrotic effects in bleomycin-induced dermal fibrosis, in Tsk-1 mice and in mice overexpressing a constitutively active TβRI. Dermal thickness, number of myofibroblasts and hydroxyproline content were all significantly reduced on treatment with 17-DMAG. No toxic effects were observed with 17-DMAG at antifibrotic doses. Conclusions: Hsp90 is upregulated in SSc and is critical for TGF-β signalling. Pharmacological inhibition of Hsp90 effectively blocks the profibrotic effects of TGF-β in cultured fibroblasts and in different preclinical models of SSc. These results have translational implications, as several Hsp90 inhibitors are in clinical trials for other indications.